Pengaruh Kepemimpinan Transformasional, Budaya Kerja Dan Motivasi Kerja Terhadap Kinerja Guru Pada Masa Pandemi - Selvi Novalianti; Sri Setyaningsih; Griet Helena Laihad (Universitas Pakuan, 2022)
THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, WORK CULTURE AND WORK MOTIVATION ON TEACHER PERFORMANCEThis Study aims to formulate concrete efforts to improve teacher performance based on a study of the influence between: (1) transformational leadership on teacher performance (2) work culture on teacher performance (3) work motivation on teacher performance (4) transformational leadership on motivation work (5) work culture on work motivation. This research was conducted in PAUD, Central Bogor District, Bogor City. This research was conducted using quantitative methods with a path analysis approach. The population in this study were private PAUD teachers in Central Bogor District as many as 187 people. The research sample was 128 people obtained by simple random sampling. The results of the study at a significant level of 5% showed that: (1) transformational leadership had a positive effect on teacher performance where the correlation coefficient was ry1= 0.298, and transformational leadership contributed 8.9% on teacher performance (2) work culture had a positive effect on teacher performance by correlation coefficient ry2 = 0.334 and work culture contributed 11.2% to teacher performance (3) work motivation had a positive effect on teacher performance as indicated by the correlation coefficient ry3 = 0.322, and work motivation contributed 10.4% to teacher performance ( 4) transformational leadership had a positive effect on work motivation where the correlation coefficient was rx3.1 = 0.443, and transformational leadership contributed 19.6% to work motivation (5) work culture had a positive effect on work motivation where the correlation coefficient was rx3.2 = 0.311, and culture employment contributed 9.6% to work motivation (6) transformational leadership had an indirect effect on teacher performance through work motivation with zcount 2.45 1.96 (7) work culture had an indirect effect on teacher performance through work motivation with zcount 2.98 1.96. Based on the results of the study, it can be seen claerly that transformational leadership, work culture and work motivation have an effect on teacher performance. There is indirect influence of transformational leadership and work culture on teacher performance through work motivation as well.